Negotiating Spirituality in Sustainable Collectives: A Case-Study of Two Multi-Spiritual European Ecovillages - Bruehwiler, Nadine ca. 20./21. Jh. (Journal for the study of religion, nature and culture, 2025)
Spirituality is increasingly seen as bearing potential to support transitions toward more sustainable behavior. However, knowledge about how sustainable collectives including members who identify as spiritual and nonspiritual negotiate this diversity to ensure their sustainability goals is limited. Applying a lived religion approach, this article addresses this gap based on an instrumental qualitative case study of two European ecovillages which include members holding diverse spiritualities and members who do not identify as spiritual. The analysis of fieldwork data regarding how spirituality becomes manifest in community narratives, rituals, pro-environmental behaviors, and materiality shows that spirituality is not important for the ecovillages as collective actors for sustainability - but spirituality matters to be a sustainable collective. Core to negotiating diversity related to spirituality are inclusively designed shared practices that rely on the communities' narratives and foci. Based on these findings, this study argues for a more fine-grained analysis of the role of spirituality for collective action for sustainability in contexts of deep diversity related to spirituality.